Capital social e capacidade funcional de idosos muito idosos que vivem nacomunidade - Alice Maria Silva (2017)
Brazil has experienced a rapid demographic transition and is now considered an aging country. Aging should be a positive experience and for this to happen, one must be vigilant about the aspects that determine healthy aging, such as the preservation of functional capacity. Among the possible factors that can influence the functional capacity of the elderly is the social capital that in this study was considered the result of the analysis of its six dimensions: groups and networks, trust and solidarity, collective action and cooperation, information and communication, social cohesion and inclusion, authority and political action. The objective of this study was to compare the social capital between functional capacity levels, and to verify if there is na association between functional capacity and social capital of oldest old people living in community. An Exploratory cross-sectional population-based study that integrates the longitudinalstudy on active aging, quality of life and gender, called Aging, Gender and Quality of Life (AGEQOL). The performance of Basic Activities of Daily Living (BADL) - Katz Scale - and Social Capital - Integrated Questionnaire to Measure Social Capital of the World Bank (IQ-SC) were evaluated. The elderly were classified as: independent, dependent partially or completely dependent and as having low or high social capital. Data analyzes included measures of central tendency and dispersion, absolute andrelative frequency, chi-square test and association between variables by Kendall's correlation coefficient (p <0.05). A total of 624 elderly people, aged over 75 years, were divided into two groups, 75-85 years old and 85-85 year olds. The mean age was 81.01 ± 5.48 years, and women were the majority (61.5%). The analyzes in this study provided evidence that the elderly population investigated was largely independent in both groups. The social capital in the total sample and in the 75-85 age group did not present a statistically significant difference when compared to the three levels of functionality. Conversely, a difference was revealed in the group of the elderly over 85 years. The prevalence of low social capital was among the elderly with partial or complete dependence, while those with high social capital, from this age group, were able to perform their BADL without restrictions. Finally, there was a low magnitude correlation between social capital and functional capacity in the age group above 85 years. This study showed that the oldest old had preserved functional capacity to perform the BADL and the association between social capital and functional capacity in the age group above 85 years. These results highligth the need to broaden the research related to social capital and the functional capacity in old age